Classificação de alunos no ensino fundamental: a imputação do fracasso ou sucesso a alunos do ciclo II - Lara, Patrícia Tanganelli (2008)
This study analizes the scolastic inclusion and exclusion of students in the 8th grade, verifying the reasons for which the students present scolastic success or weakness. The main objective of the research was to identify and characterize scolastic inclusion and exclusion of students at the end of the eight grade in relation to the organizational aspects of the school and the curiculum being used at the school, as seen through the work of the teachers, as well as in relation to the social and cultural characteristics of all the school employees. The main theoretical references for the present study were Bourdieu, in order to comprehend the meaning of the categories allotted by the teachers for the students and those excluded from the interior; Charlot, to clarify the relation to knowledge; and Lahire, to discuss the scholastic success amongst the lower-class population. To explain the processes of selection existent in the day to day school environment, Apple was consulted. The data collected refers to observation within the school, including the 8th grade students of a public school situated in the city of São Paulo em 2007; to the questionaires applied to and interviews with teachers and students throughout the time period; and to the analysis of documents related to the evaluations of the students when in the 8th grade and prior (when in the 4th grade), and other information from general evaluation tests, and from scolastic organization. The results indicate that the production of scholastic success or weakness was an institutional factor, including the actions of all school employees, be it by the classification used, be it by the maintenance of them throughout the years, be it by the institutions that decided the lives of the students, and be it by the actions of the team of directors in omitting many times the conditions or change in conditions needed for betterment and not providing substitution rather than suspension of so many classes, which only worsened the precariousness of the attention given. These actions within the school demonstrate strong traits of school culture, which proportions the scholastic inclusion or exclusion of students